Evaluation of the probiotic and functional potential of Lactobacillus agilis 32 isolated from pig manure. (8th April 2021) - Shi, S.; Cheng, B.; Gu, B.; Sheng, T.; Tu, J.; Shao, Y.; Qi, K.; Zhou, D.
Abstract: Escherichia coli is a symbiotic bacterium in humans and animals and an important pathogen of humans and animals. Prevention and suppression of E. coli infection is of great concern. In this study, we isolated a strain of Lactobacillus agilis 32 from pig manure and evaluated its biological characteristics, and found that its bacterial survival rate was 25% after 4 h of treatment at pH 2, and under the condition of 0·5% bile concentration, its survival rate exceeds 30%. In addition, L. agilis 32 has a cell surface hydrophobicity of 77·8%, and exhibits 67·1% auto‐aggregation and 63·2% aggregation with Enterotoxigenic E. coli 10 (ETEC 10). FITC fluorescence labelling showed that the fluorescence intensity of cecum was significantly higher than that of duodenum, jejunum or colon ( P < 0·05), but no significant difference from ileum. Lactobacillus agilis 32 bacterial culture and CFS showed average inhibition zone diameters of 14·2 and 15·4 mm respectively. Lactobacillus agilis 32 CFS treatment can significantly reduce the pathogenicity of ETEC 10. These results show that L. agilis 32 is an active and potential probiotic, and it has a good antibacterial effect on ETEC10, which provides basic research for probiotics to prevent and treat intestinal diarrhoea pathogen infection. Abstract : Significance and Impact of the Study: Lactobacillus agilis 32 tolerates bile and low pH and is able to stably colonize the entire intestinal tracts of chickens. Bacterial cultures and cell‐free supernatant of L. agilis 32 inhibited ETEC 10 growth. Lactobacillus agilis 32 can significantly reduce the pathogenicity (exercise, biofilm and virulence factor expression) of ETEC10 and destroy the complete structure of the bacterial cell and the synthesis of the protein. Therefore, L. agilis 32 isolated from pig manure has probiotic potential and inhibits the growth of ETEC 10.